lshʾlt hmvnh ṿhsdr shl "frḳy vʾṿry hshmṿt" vmṿrh nvṿkhym / The Structure of the Lexicographic Chapters in the "Moreh Nevukhim" - Turner, Masha (Hebrew Union College annual, 1991)
The bulk of the first part of Maimonides' Guide for the Perplexed consists of lexicographic chapters, i.e., chapters devoted to a philosophical exegesis of Biblical terms (Guide I:1—49, 61—70). The author's object in these chapters is to explain away any hint of anthropomorphism that might be implied by the Biblical text. We propose a theory which explains the specific choice of the fifty-four terms listed in the lexicographic chapters, the structure of the list, and the order of the terms within it. In Guide I:46, Maimonides lists the divine attributes: existent, living, possessing knowledge and power, and active — a list common to those holding that God has positive attributes. It is our contention that the Biblical terms explicated in the lexicographic chapters can be classified into four groups: "existent" (chaps. 1—7); "living" (chaps. 8—43); "knowledge" (chaps. 44—48); and "power-action" (chaps. 65—70). Each group contains terms used to describe God and associated with one specific attribute. An attempt is made to explain and clarify the specific choice of terms in each group and their order within the group. It is noteworthy that Maimonides' treatment relies, at least technically, on the Kalam doctrine that God has positive attributes, although his own esoteric view denies the very possibility of predicating positive attributes of God. A possible explanation for this apparent contradiction is that the exegetical portion of Guide of the Perplexed is not esoteric, being intended inter alia for the common people (Guide I:35).